Arqueología y téchne : métodos formales, nuevos enfoques = Archaeology and techne : formal methods, new approaches - Remesal Rodríguez, José; Pérez González, Jordi (Access archaeology., 2022)
This work presents papers resulting from the EPNet project (Production and Distribution of Food during the Roman Empire: Economic and Political Dynamics) which aimed to investigate existing hypotheses about the Roman economy in order to understand which products were distributed through the different geographical regions of the empire, and in which periods.